'Arianism' Ante Litteram in Origen's Peri Archōn 4.4.1. (19th July 2021) - Ip, Pui Him
Abstract: In Peri Archōn 4.4.1, Origen argues against a form of 'Arianism' ante litteram . Previous scholarship has suggested that the view targeted by Origen could be a form of Basilidean system. In this paper, I make a fresh attempt to identify the polemical context of this passage. I first identify a more reliable control for delimiting the possible targets using Origen's classification of heresies reported in Pamphilus' Apology and Book 32 of the Commentary on John . Synthesis of the two reports suggests that Origen is unlikely to have targeted Basilides' teachings in Peri Archōn 4.4.1. I then analyse two further pieces of evidence to substantiate an alternative identification: psilanthropism or monarchianism. Where Origen explicitly rejects ἦν ποτε ὅτε οὐκ ἦν (or variants), one finds these two positions as the immediate polemical context. Further, analysis of Peri Archōn 1.2.1–4 reveals that, as in Peri Archōn 4.4.1, these positions are placed alongside Valentinian emanationism as the twin polemical targets of Origen's Christology. This fresh identification opens up a new perspective for reassessing the development of the fourth-century 'Arian' controversy prospectively, that is, through the lens of the third-century polemical landscape.